O réu e a vítima: projeção de imagens na série "Coisa mais linda" - Bruna Carvalho Zarattini (2023)
The internet drives the emergence and adaptation of discursive genres, since it impacts the action fields, as demonstrated by Bakhtin, Bazerman (2020) and Maingueneau (2015; 2017). In this sense, we note the effusion of the discursive genre series, especially when we check the volume of productions coming from streaming services nowadays. Among many contemporary titles belonging to this genre, there is the series Coisa mais linda, from the catalog of the on demand service Netflix. This Brazilian production stands out for portraying the daily lives of four women, located in Brazil between 1950 and 1960, who face daily prejudice and gender violence, just as, off screen, women of the 2020s still face in their. Considering the two seasons of the title, since the narrative proposes to deal with prejudice and gender violence, it is understood that the key point of the plot concerns the trial of the character Augusto, for the murder of his wife, Lígia. Thus, in the light of Argumentation in discourse (AMOSSY, 2018a), we analyze the discursive images, projected by themselves and the other (AMOSSY, 2016b; LIMA, 2006; MAINGUENEAU, 1997; 2004; 2008; 2015; 2016; 2018) – focusing on images of the defendant and the victim –, in the Jury Court within the series. And, furthermore, facing the fact that socially prevailing values guide the images built in staged tribune, a relationship is established between fictional universe and real, contemporary Brazil. Because audiovisual productions can represent and have the ability – to some extent – to impact society, making it better seen and also leading to structural changes.